Application of Life Cycle Assessment (LCA) to cereal production: an overview. Issue 1 (1st September 2022) - Vinci, G; Ruggieri, R; Ruggeri, M; Zaki, M G
Abstract: Cereals have been the basis of human and animal nutrition for centuries, and according to the Intergovernmental Panel on Climate Change (IPCC) (2020), between 1961-2019 their global production increased by +240%, reaching about 3 billion tons, accounting for 18% of climate-changing emissions from the agro-food sector. Continued population growth will lead to the need to produce more food, and to keep up it is estimated that cereal production will need to increase by 900 million tons by 2050, posing an inevitable increase in environmental pressures. Therefore, the new challenge will be to reconcile increased production with sustainable agricultural practices, in line with the Sustainable Development Goals (SDGs) and the new Common Agricultural Policy (CAP). Since cereal production is essential to produce globally relevant commodities, it is important to assess and study its associated environmental effects. In this context, the Life Cycle Assessment (LCA) is recognized by the international scientific community as a useful tool for the assessment of environmental impacts caused by products, processes or systems and for the validation of new production paradigms. Therefore, the aim of this research is to carry out an overview of the literature on the most recent applications of LCA related to the production of cereals, in order to highlight the main criticalities, also according to the different production methods of the various Countries. Therefore, the three major cereals (corn, wheat and rice) and five minor ones (barley, sorghum, millet, oats and rye) were considered and the results showed that for all crops the main hotspot is the application and use of fertilizers. However, studies often differed in terms of functional unit, impact assessment methods, and respective environmental indicators. Therefore, a complete comparison was not always possible. Finally, the literature overview did not identify studies in which the social impacts of cereal production were considered, although economic assessments are present in some cases. Therefore, it is believed that consistent with the achievement of the SDGs, it is desirable to apply Social Life Cycle Assessment (S-LCA) in agricultural and development policies to consider not only environmental impacts, but also economic and social impacts, in order to ensure a truly sustainable development and thus on all three dimensions